PENGARUH DESAIN PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN TAS ELIZABETH DI SURABAYA TIMUR - Suryandari, Septi Eka; Maduwinarti, Ayun; Novaria, Rachmawati (Jurnal Dinamika Administrasi Bisnis, 2016)
Elizabeth bag products are brand bag that has become the symbol of â€œprestigeâ€ for lovers bags. A brand bags are already quite prominent in Indonesia. In this study tried to see how much influence variable product design and quality of the purchasing decision. The sample used was the visitors who shopped in the store bag Elizabeth Surabaya and aged 18 years and older. The results showed the product design and product quality and significant positive influence on purchasing decisions and product quality vareabel the dominant influence on the purchase decisions.Â Keyword: Design product, quality product, purchasing decisions